Building the Sustainability of the Kopeci Tofu Business through Consumer Interaction, Food Taste, and Price Suitability - Nur Azizah, Dina; Yusrina, Aida; Devino, Troya Ensa; Wachdijono, Wachdijono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Business sustainability shows the existence of a business wherever it is, so it is always a goal that business actors, including Tofu and Kopeci businesses, must achieve. However, achieving this business is not easy because many factors influence it. This research explores the influence of social media, products, and prices on the desire for Kopeci tofu businesses. The study was conducted in Kuningan Regency, West Java Province, Indonesia, from May to July 2024. The research design was quantitative, using survey methods. Accidentally sampling determined the sample size of 146 Kopeci tofu consumers. Variable indicator measurements use a Likert Scale, and data analysis uses Structural Equation Modeling. The research results show that there is a mediation series, namely that social media directly affects the product, the product directly affects the price, and the price directly affects interest in the Kopeci tofu business. The most dominant indicator in explaining the condition of the social media variable is "interaction", the product variable is "good taste," and the price variable is "price according to the brand". Therefore, it is recommended for kopeci tofu businesses in Kuningan Regency and surrounding areas to always communicate regularly with consumers, maintain the taste of kopeci tofu, and always maintain the product brand image on the market to maintain the desire for kopeci tofu